The Calorific Value Experiment on Coconut Shell, Bamboo and Mixed Charcoal Briquette - Siharath, Phoummixay; Chanthakhoun, Metkham; Kannitha, Soulyphan; Sonemanivong, Chankhachone; Vilaychaleun, Somchay; Thammathevo, Khampasith; Siharath, Phaiphana; Phommakone, Bounmy; Kounlaxay, Kalaphath; Inthaphouthone, Pathana; Leuanglith, Youlananh (Darul Yasin Al Sys, 2024)
The utilization of biomass waste to produce energy is an alternative to get rid of wastes and also save the environment, charcoal briquette is a significant energy and potential choice to use in households, restaurants, markets and other cooking activities, because, it is very easy and convenient to use. The objective of this study is to research on calorific value of charcoal briquettes in various different material. Therefore, according to the experiments found that, the calorific value results of coconut shell briquettes (CBr1), bamboo charcoal briquette (CBr2), mixed charcoal briquette (CBr3) are 6,682 MJ/kg ,4,880 MJ/kg and 5,433 MJ/kg, and remaining ashes are 77 g, 100 g and 250 g, respectively. Apparently, the coconut shell briquette is more preferable and less remaining ashes on environment than other materials.